Harlequin Ichthyosis: A Case Report - Shoaib Akhtar; Adeel Anwaar; Inam Ul Haq; Hazaq Mukhtar; Sabir Jamal; Muhammad Muzammil; Aymar Akilimali (Clinical Case Reports)
ABSTRACT Harlequin ichthyosis (HI) is a genetic disorder caused by ABCA12 gene mutations, presenting with thick, scaly skin and deep fissures. Early recognition, intensive neonatal care, and multidisciplinary management are crucial for improving survival and quality of life. Treatment focuses on skin hydration, infection prevention, and supportive care to manage symptoms effectively.